Polyarteritis nodosa presenting with severe upper gastrointestinal bleeding: a case report - Xin-Yue Xiao; Yun Niu; Ping-Ping Liu; Yu-Ming Zheng; Ming-Gang Zhang; Guo-Chun Wang; Xiao-Di Wang; Fang Liu (Journal of Medical Case Reports)
Abstract Background Polyarteritis nodosa is a relatively uncommon type of systemic necrotizing vasculitis that primarily affects medium-sized arteries. While gastrointestinal involvement is known in polyarteritis nodosa, heavy gastrointestinal bleeding due to gastric ulceration is relatively uncommon. We present the case of an 81-year-old male of Chinese ethnicity who experienced severe gastrointestinal bleeding as a result of polyarteritis nodosa and an innovative treatment approach for a better patient outcomes. Case presentation Upon admission to the medical intensive care unit, the patient underwent a comprehensive diagnostic assessment, including examinations for cardiovascular and dermatological abnormalities, laboratory tests, autoantibody and tumor marker assessments, and imaging studies (such as endoscopies, whole-body computed tomography, and positron emission tomography–computed tomography scans), and a skin biopsy. The patient had tachycardia, hypotension, and extensive skin abnormalities on the lower extremities along with anemia, low platelets, and abnormal renal function. Upper gastrointestinal endoscopy revealed gastric and duodenal ulcers. Additional examinations, including electronic colonoscopy, capsule endoscopy, and whole-body computed tomography, were negative. A positron emission tomography–computed tomography scan showed increased uptake in the arterial walls and skin, which supported the diagnosis of polyarteritis nodosa, later confirmed by a biopsy of the skin on the lower extremities. Methylprednisolone, octreotide, and omeprazole were administered, leading to improvement in gastrointestinal symptoms, ulcer healing, and skin recovery. The patient continued with prednisone for 1 month. Conclusion This case serves to inform gastroenterologists about the need to consider polyarteritis nodosa in severe upper gastrointestinal bleeding and underscores the importance of prompt, medication-based treatment for successful patient outcome.